Comparative study of Euler’s method and Runge-Kutta method to solve an ordinary differential equation through a computational approach - Paudel, Dharma Raj; Bhatta, Mohan Raj (Academic Journal of Mathematics Education, 2023)
Euler’s and Runge-Kutta’s methods are used to solve ordinary differential equations. Euler’s methods become appropriate method for solving the equations. When the steps are small, they give reasonably accurate results. However, if the steps are not so small, the Runge-Kutta method is preferred to solve the problem. This paper uses the Python program to show the results of both methods. This computational approach shows that the Runge-Kutta method is better for small steps at solving differential equations than Euler’s method.